Recent Advances in Physicochemical Control and Potential Green Ecologic Strategies Related to the Management of Mold in Stored Grains - Tianyu Sha; Yujie Lu; Peihuan He; Md Mehedi Hassan; Yehan Tong (Foods)
Grain serves as an essential cornerstone for sustaining life and social stability. However, during storage grain is often invaded by mold, which leads to mildew issues. This problem diminishes nutrient content and food quality and raises safety concerns, including toxin production, which can cause serious economic losses and catastrophic market stability and national food security conditions. Accordingly, implementing effective measures to prevent and control mold is crucial for ensuring grain storage safety. This paper analyzes the molds that affect grain during storage, discussing their varieties, environmental needs, and potential hazards. It also expounds on corresponding prevention and control measures, including physical methods, chemical approaches, innovative mold inhibitors derived from microbes and plants, and micro–nano prevention and control technology. These measures demonstrate significant mold suppression by destroying the cell structure of mold or inhibiting its physiological processes. In particular, micro–nano technology enables the effective embedding and controlled release of active ingredients. It can prolong the release duration and enhance antibacterial stability, thus achieving more effective control effects. Furthermore, it can be concluded that these strategies provide a theoretical foundation to enhance the safety and efficiency of grain storage. Additionally, they assist in more effectively addressing mold-related challenges while ensuring food security.